Crystal structure, microbiological activity and theoretical studies of Ag(I) and Cu(I) coordination polymers with 1, 1′-(butane-1, 4-diyl)bis(3-methylimidazoline-2-thione) ligand. (28th May 2016) - Beheshti, Azizolla; Babadi, Susan Soleymani; Nozarian, Kimia; Heidarizadeh, Fariba; Ghamari, Narges; Mayer, Peter; Motamedi, Hossein
Graphical abstract: Two new coordination polymers of the bbit ligand with Ag(I) and Cu(I) ions have been successfully synthesized by one-pot reactions. Coordination modes of the bbit ligand and size of the metal ions play a major role in determining the final structure of these compounds. Abstract: Reaction of 1, 1′-(butane-1, 4-diyl)bis(3-methylimidazoline-2-thione) (bbit) with appropriate silver(I) and copper(I) salts at room temperature leads to the formation of {[Ag(μ2 -bbit)](BF4 )} n (1 ) and {[Cu2 (μ-bbit)3 ](PF6 )2 } n (2 ) coordination polymers. These compounds have been fully characterized by using the single crystal X-ray diffraction, XRPD, TGA, elemental analysis, infrared spectroscopy, antibacterial activity and molecular docking studies. Crystal structure of (bbit) shows that the molecule has a center of symmetry lies at the mid-point of the (CH2 )4 spacer between the two imidazole-2-thione rings. In the cationic 3D structure of1, silver atom has a distorted tetrahedral coordination geometry and each of the centrosymmetric μ2 -bbit ligands with an anticonformation bridging two crystallographically related silver atoms to form a double-bridged Ag(μ2 -S)2 Ag core as a basic building block. Coordination mode of the bbit ligands and geometry around the metal ions in polymers1 and2 are different. Each of the copper atoms in2 has a trigonal planar CuS3 environment and μ-bbit act as a bridging bidentate ligand, so that two of the CuS3 motifs are interconnected by a pair of μ-bbit ligands through the thione sulfur atoms to generate a 22-membered [Cu2 (μ-bbit)2 ] 2+ ring. The adjacent [Cu2 (μ-bbit)2 ] 2+ cores are linked by a single μ-bbit ligand to form a 1D chain structure. Additionally, the adjacent 1D chains are extended into a non-covalent 3D network structure by the intermolecular PF…H hydrogen bonds. The in vitro antibacterial studies of bbit, polymers1 and2 showed that, polymer1 was able to inhibit growth of the tested bacteria, whereas the bbit ligand has a weak and polymer2 showed no antibacterial activity against these bacteria.